Mascarimirì, come legge! Schooling, identity and reworking of cultural affiliations in the inter-generational story telling of south Italian Rom family. Notes on an ongoing investigation - Ciniero, Antonio (Rivista di Storia dell’Educazione, 2017)
In Salento, presences of the Roma people has bee formally recorded since the 16th century, and still today a large number of Roma origins families is living there. Their history is deeply intertwined with the local one. Through the analysis of historical and anthropological sources and ethnographic interviews, this paper describes the processes of exchange and interaction between a Roma family and the broader socio-economic context, with a particular attention to the role of schooling processes.